Credit default swaps and corporate debt structure - Chen, Yangyang; Saffar, Walid; Shan, Chenyu; Wang, Sarah Qian (Journal of Corporate Finance, 2023)
Whether and how credit default swaps (CDSs) affect corporate debt structure remains an unanswered question. We find that firms use more public debt relative to bank debt when CDSs referencing their debt start trading. The results are robust to the endogeneity of CDS trading. Furthermore, the increase in public debt is concentrated in senior bonds and notes, which are the most common CDS reference assets. The effect of CDS trading is most pronounced when bond underwriters take a net selling CDS position and for informationally opaque firms. These findings suggest that the hedging and informational roles of CDSs have real effects on corporate debt structure.